“A La Ursa quer dinheiro, quem não dá é pirangueiro”: changes in the carnival of La Ursas in São Caitano-PE (Orfeu, 2021)
La Ursa is a carnival brincadeira in the Northeast of Brazil. The main character is a Urso (Bear). It is common to find this expression in the state of Pernambuco. With the many changes in society, La Ursa has also changed, including its sound and its music. This paper aims to describe and discuss the history of La Ursa in São Caitano-PE, pointing to the transformations of brincadeira during the carnival in its city. We conducted interviews with the president of the Association of La Ursas of São Caitano and with other people involved with the history and the changes of the brincadeira. The transformations necessary to ensure the existence of the La Ursa are mainly linked to economic, political, and cultural factors.